Arthroscopic Repair of Rotator Cuff Tears by Human Dermal Allograft Reconstruction vs Maximal Repair. Issue 7 (31st July 2020) - Xu, Jian; Ravipati, Anjaneyulu Purnachandra Tejasw; King, John-Paul; Coady, Catherine; Wong, Ivan
Objectives: To determine healing rate of rotator cuff reconstruction with an acellular human dermal allograft compared with the gold standard arthroscopic maximal rotator cuff repair of large, chronic tears of the rotator cuff. Methods: Thirty patients with a two-tendon chronic retracted rotator cuff tear were enrolled in the study and were randomly allocated (15) to each group. All the patients were evaluated for structural integrity of repair using a 1.5T MRI at an average of 15 months after surgery. Rotator cuff arthropathy (RCA) and acromio-humeral distance (AHD) were graded using X-rays. Western Ontario Rotator Cuff (WORC), Disabilities of the Arm, Shoulder, and Hand (DASH), Marx Activity Rating Scale (MARX) scores, range of motion (ROM) of shoulder were analyzed. Results: The re-tear rate in the reconstruction group was 13% (2 of 15 patients) compared to 73% (11/15) in the repair group (p=0.008). Progression of RCA was seen in 7% (1/15) and 35.71% (5/15) of patients in the reconstruction and repair group, respectively (p=0.006). The change in AHD (preop-postop) was significantly higher in the repair (reduced by 2.27 mm) than the reconstruction group (increased by 0.1 mm) (P=0.006). Both groups had significant improvements in patient reported outcome scores. The reconstruction group had statistically significant better forward flexion (p= 0.01) and scapular plane abduction (p=0.03) compared to the repair group. Conclusions: Rotator cuff reconstruction with a dermal allograft demonstrated favorable structural healing rates and improved range of motion compared to maximal repair in the short term. Moreover, the maximal repair group were more likely to develop RCA than reconstruction. Angle at which apprehension disappears Less than 60 degrees (n = 55) 60 degrees or more (n = 21) Significance Caton-Deschamps Index 1.12 ± 0.12 1.19 ± 0.19 P = 0.036 Trochlear Dysplasia P < 0.001 None or Dejour A 50 (91%) 10 (48%) Dejour B, C, or D 5 (9%) 11 (52%) Sulcus Angle (degrees) 156 ± 12 168 ± 17 P < 0.001 Sulcus Depth (mm) 2.5 ± 1.5 1.2 ± 1.7 P = 0.002 TT-TG Distance (mm) 18.3 ± 7.3 24.6 ± 10.3 P = 0.004